ANALYSIS OF TRANSLATION SHIFTS IN VERB PHRASES AND THE IMPACT ON SINGABILITY AND SENSE IN MAMMA MIA! HERE WE GO AGAIN (2018) - Nisrina Firyal Prilandhia; Ina Sukaesih; Farizka Humolungo (Politeknik Negeri Jakarta, 2025)
This study examines translation shifts in verb phrases and their impact on the singability and sense of song lyrics in the subtitles of the musical film Mamma Mia! Here We Go Again (2018), available on the Max streaming platform. Based on Catford’s (1965) theory of translation shifts and Low’s (2017) translation song criteria of singability and sense, this study analyzes how shifts in verb phrase structure affect the musical and narrative integrity of translated lyrics. 18 songs from the film were selected for analysis. The study categorizes the translation shifts into unit, class, structure, and intra- system shifts and evaluates whether these shifts preserve or alter the original meaning and performability of the lyrics. The findings highlight the challenges of subtitle translation in musical films and offer insights for preserving the emotional and musical experience in the target language. Keywords: translation shift, verb phrase, singability, sense, musical film